Cause And Effect Of Delay Selected Building Construction At Adama Town - Daniel, Lema (My University, 2017)
Delays are one of the biggest problems construction firms face. Delays can lead to many negative effects such as lawsuits between owners and contractors, increased costs, loss of productivity and revenue, and contract termination. Even though various studies have been considered into the causes affecting delays, these studies seldom discuss common and general causes of delays in construction projects . a construction contract is made between two parties only, i.e the employer and the contractor. Their roles are defined in the contract. However, because there is a need for day-today supervision of civil engineering, construction, the two parties may agree that third person should carry out such duties. This third person can have varying powers under the contract and this is reflected in his designation .he can be designated the engineer Under the contract; or he may be designated The project manager or employers mployer representative In both cases occupying a distinctly different position from any other designation. The results obtained indicate that the top major causes of delay were; design change, contract modify, fluctuation of prices of construction materials, project schedule change. In addition the top major effects of delay were; time overrun, cost overrun, total abandonment and dispute. The construction industry in adama town is an important sector due to its enormous contribution to the town economic development. This in terms of employment opportunities and attraction of foreign direct investments which grossly contributes to the town. However due to social and financial situation of the town, many construction projects are prone to delay. These delay factors can only be avoided by first identifying the factors and their source. A survey on project management performance of different types of construction projects in adama town was conducted to determine the causes of delays which are one of the major source of disputes and Construction claims And their importance according to each of the project participants, i.e. owner, consultant and the contractor. The main purpose this paper to find out the main cause of delay in building construction in adama